INTERPRETATION OF PSYCHOLOGICAL KNOWLEDGE IN THE TEACHINGS OF OUR GREAT ANCESTORS - Sadullaev, Azamat Nafiddinovich (Educational Research in Universal Sciences, 2022)
Thanks to independence, the work on improving the sciences in the field of education is developing rapidly. Every social system has concepts such as education, spirituality and enlightenment that ensure the spiritual growth of man, which require a comprehensive study of changes in pedagogical psychological sciences in relation to the development of society. Mastering these sciences requires a thorough knowledge of the ideas about human perfection, its spiritual development, which is the driving force of spiritual, social, political and economic life.